Subterranean - Rollins, James, 1961- (New York : Avon Books, 1999)
Beneath the ice at the bottom of the Earth is a magnificent subterranean labyrinth, a place of breathtaking wondersand terrors beyond imagining. A team of specialists led by archaeologist Ashley Carter has been hand-picked to explore this secret place and to uncover the riches it holds. But they are not the first to venture hereand those they follow did not return. There are mysteries here older than time, and revelations that could change the world. But there are also things that should not be disturbedand a devastating truth that could doom Ashley and the expedition: they are not alone.
Keywords: Voyages to the other world; Voyages, Imaginary; Science fiction; Sea stories; Adventure fiction